Effects of breathing exercises using home-based positive pressure in the expiratory phase in patients with COPD. Issue 1127 (22nd July 2019) - Lin, Qibin; Zhuo, Leying; Wu, Zhenjie; Li, Chengye; Zhou, Meixi; Cai, Chang
Abstract: Background: Patients with chronic obstructive pulmonary disease (COPD) commonly have higher intrinsic positive end-expiratory pressure (PEEPi). A breathing exercise programme strategy employing an appropriate PEEP may improve their pulmonary functional capacity, exercise tolerance and health-related quality of life. Breathing with an expiratory resistive load, which is a method of modulating spontaneous breathing against PEEPi, has not been fully studied in patients with COPD. The objective of this study was to investigate the role of changing spontaneous breathing in home-based conditions and regulating spontaneous breathing with breathing exercises in patients with COPD. Methods: This was a prospective randomised trial including 64 patients with a diagnosis of stage III or IV COPD. Patients were randomised into two groups: standard treatment and standard treatment combined with breathing exercise rehabilitation. The effects of the treatments on the COPD assessment test (CAT) score, 6-minute walk test (6MWT) results and pulmonary function were compared at 0, 6, 12 and 18 months within and between the two groups. Results: All outcomes showed no significant differences between the two groups at the beginning of the study, while the 6MWT and CAT scores exhibited clinically and statistically significant improvements (p<0.001) by the end of the study. At month 18, the change in the predicted percentage of forced expiratory volume in 1 s (FEV1 %pred) differed between the two groups (p<0.05). In addition, there were statistically significant differences in the 6MWT results, CAT scores and FEV1 %pred values between the baseline and month 18 (p<0.0001) in the intervention group. Conclusions: Improvements in 6MWT results, pulmonary function and CAT scores are associated with a successful response to breathing against PEEPi in patients with COPD. Trial registration: This trial was registered at research registry.com (identifier research registry 4816).